Effect of intermediate-term firewood smoke air pollution on cardiometabolic risk factors and inflammatory markers - Lanas, Fernando; Saavedra, Nicolás; Saavedra, Kathleen; Hevia, Montserrat; Seron, Pamela; Salazar, Luis A. (Frontiers in Cardiovascular Medicine, 2023)
Background: Temuco is a city in Southern Chile with elevated levels of air pollution (AP), mainly due to using wood as combustion throughout the cold season. The study aimed to assess the differences in cardiometabolic risk factors, estimated cardiovascular risk, and blood level of inflammatory markers between high AP (HAP) and low AP (LAP) periods.Methods: A prospective panel study was conducted between January to September 2018. Air pollution was assessed by PM2.5 concentration. Ninety individuals from the general population were included in the study. Measurements were performed in the HAP and LAP, including medical history and lifestyle, physical activity assessment, physical exam, and fasting blood samples for glucose, lipids, and circulatory inflammatory mediators.Results: in the high air pollution period, systolic blood pressure was 3 mmHg higher (p=9.05).HDL-cholesterol was 14.2 mg/dL lower (p<0.001), Framingham risk score increased from 14.5 to 18.0 (p<0.001), and highly significant lower levels of interleukins, MCP1, MMP1, MMP2, sICAM, and svCAM were observed.Conclusions: HAP was associated with increased cardiometabolic risk factors and estimated cardiovascular risk. However, a lower level of circulating acute inflammatory molecules was observed. Inflammatory molecules blood levels were not associated with changes in cardiometabolic risk factors.